G284(P) CHip: Child health information for parents – animated health education videos for the waiting area. (24th May 2017) - Knight, KM; Trehane, SJ; Chingono, J; Crossley, B; Cleugh, F
Abstract : Aim: A high proportion of Emergency Department attendances are driven by parental anxiety over minor childhood illnesses, and often parents are unaware of simple home interventions that could have been trialled before seeking medical advice. We aimed to provide child health information videos designed to play in paediatric waiting areas, delivering simple messages about managing illnesses at home, and providing details of alternative ways of seeking medical advice that do not involve an Emergency Department visit. Method: Three animated videos were created, giving basic information regarding fever, gastroenteritis and meningitis. Each video was under three minutes in length, and all information was displayed in text and picture format without sound. The content was based on NICE guidance. Each video ended with showing alternative means of seeking advice (including NHS 111, walk in centres and the NHS Choices website). The videos were shown to parents in the A and E waiting room and in paediatric outpatients, and they were asked to complete a feedback questionnaire immediately after viewing. Results: Twenty-seven parents were shown the videos. Feedback was overwhelmingly positive, with comments such as 'the videos were clear and informative' and 'easy to understand'. 22 respondents said that the information in the video would influence their behaviour next time their child was sick, for example 'I would follow the steps in the video' and 'am more confident in signs to look for'. 22 respondents said they would view the videos again at home if available on the internet; 25 would recommend to other parents; 22 would like to see the videos in an A and E waiting area and all 27 said that they would like the videos in a clinic waiting area. Parents had valuable suggestions for future topics, including asthma, vaccinations and nutrition. Discussion: The videos are being developed further in conjunction with local parent representatives, taking into account feedback from parents to tailor content to their needs. They will initially be shown in the Emergency Department and discussions regarding showing the videos in linked GP surgeries are taking place with local GPs. Future work will include translating the video text into other common local languages.